Melon Cultivation in Sand and Hardwood Sawdust - Raja Harun, Raja Muhammad; Hall, D. A.; Hitchon, D. M.; Szmidt, R. A. K. (1992)
The growth and productivity of melons, cultivar 'Polidor', were assessed in 2, 4 and 8 litres of sand and hardwood sawdust irrigated to excess with a complete nutrient solution. The plants were grown in a glasshouse set at day/ night temperatures of lS'C/15'C with venting at 26'C. Mean total stem and leaf dry matter after the lmits were harvested were not significantly different between treatments. Mean limit yield (number and weight) was not affected l7y substrate volume but was significantly (P<O.Ol) higher from plants grown in sand. Similarly, mean harvest date for the first lmit was significantly (P<O.Ol) earlier from plants grown in sand compared with sawdust